Time to task failure of the contralateral untrained limb after high load-low repetition eccentric and low load-high repetition resistance training - Nosratollah Hedayatpour; Ali Golestani; Zahra Izanloo; Ali Sepehri; Maryam Kamali (Universidade Estadual Paulista (UNESP), 2017)
Abstract Aims: Cross-training is the process whereby training of one limb gives rise to enhancements in the performance of the opposite, untrained limb and may be dependent on type of muscle contractions performed. The aim of this study was to investigate whether unilateral resistance training using eccentric contraction is more effective than concentric resistance training to improve time to task failure in the contralateral untrained limb. Methods:Subjects completed 12 weeks of resistance training consisting of 36 sessions, using unilateral leg exercise. Sustained isometric knee extension performed at 50% of maxmal force until task failure for the contralateral untrained leg. Surface electromyography (EMG) signals were simultaneously recorded from contralateral untrained quadriceps (vastusmedialis, rectus femoris, and vastuslateralis). Results: Time to task failure of the contralateraluntrained leg and associated EMG activitiessignificantly increased after 12 weeks ofunilateral resistance training(p<0.05). However, percent increase in time to task failure and EMG amplitude after eccentric resistance training was significantly higher than concentric resistance training (p<0.05). Conclusion: This study concluded that unilateral eccentric resistancetraining is superior to concentric resistance training to increase time to task failure in the contralateral untrained limb.